2014
DOI: 10.15517/rbt.v1i2.15412
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of <i>Bacillus thuringiensis</i> strains isolated from coffee plantations infested with the coffee berry borer <i>Hypothenemus hampei</i>

Abstract: Abstract:The coffee berry borer Hypothenemus hampei Ferrari (Coleoptera: Scolytidae) was first reported infecting Costa Rican coffee plantations in the year 2000. Due to the impact that this plague has in the economy of the country, we were interested in seeking new alternatives for the biological control of H. hampei, based on the entomopathogenic bacteria Bacillus thuringiensis. A total of 202 B. thuringiensis isolates obtained from Costa Rican coffee plantations infested with H. hampei were analyzed through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…These results are in accordance with reports where foliar surfaces and insectfavoring habitats have been indicated as frequent sources of Bt isolation (Ben-Dov et al 1997, Bravo et al 1998, Arrieta et al 2004. However, this is the first report of Bt isolation from fecal pellets of caterpillars collected in tropical protected environments.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with reports where foliar surfaces and insectfavoring habitats have been indicated as frequent sources of Bt isolation (Ben-Dov et al 1997, Bravo et al 1998, Arrieta et al 2004. However, this is the first report of Bt isolation from fecal pellets of caterpillars collected in tropical protected environments.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the vip1 gene was not detected in this collection and only one strain presented the vip2 gene. Different results were obtained in a Costa Rican collection isolated from coffee plantations where the frequency of the vip2 gene was higher (Arrieta et al 2004).…”
Section: Discussionmentioning
confidence: 78%
“…Estruch et al (1996) found this gene in only 15% of the strains of their collection. Arrieta et al (2004) also reported a widespread distribution of this gene in strains isolated from Costa Rican agricultural ecosystems. In contrast, the vip1 gene was not detected in this collection and only one strain presented the vip2 gene.…”
Section: Discussionmentioning
confidence: 87%
“…Such result was certainly specific for our strains collection. For example, Arrieta et al found the vip3 gene in 74% and the vip2 or vip1 in <12% of a set of B. thuringiensis strains isolated from Costa Rican coffee agro‐ecosystems. The observed frequency of the vip3 genes was 48.9% and the vip1 and vip2 genes was around 10% of the strains isolated mainly from Spain and Bolivia .…”
Section: Discussionmentioning
confidence: 99%